Morality Without God? - Sinnott-Armstrong, Walter (Philosophy in action., 2009)
Some argue that atheism must be false, since without God, no values are possible, and thus "everything is permitted." Walter Sinnott-Armstrong argues that God is not only not essential to morality, but that our moral behavior should be utterly independent of religion. He attacks several core ideas: that atheists are inherently immoral people; that any society will sink into chaos if it is becomes too secular; that without morality, we have no reason to be moral; that absolute moral standards require the existence of God; and that without religion, we simply couldn't know what is wron.